Pengembangan Konten Edukatif untuk Sosialisasi Pencegahan COVID-19 pada Anak di Pasar Bersehati Kota Manado - Lenny Gannika; Erika Emnina Sembiring (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2021)
The children at the Bersehati Public Market in Manado City were found selling during the COVID-19 Pandemic to help their parents but they found difficult to implement health protocols. Therefore, it is very important to provide health education to children about COVID-19 prevention. This community partnership program (PKM) was carried out at Bersehati Public Market in Manado and in collaboration with the Manado City Women's Empowerment and Child Protection Service and the Manado Dinding Community which aims to provide and increase children's knowledge about COVID-19 prevention through educational content. Dissemination of COVID-19 prevention is carried out through watching educational videos, health promotion using posters, drawing & coloring. The distribution of medical masks, hand sanitizer and writing utensils to children was also carried out at this event. This PKM activity was attended by 43 children, 4 representatives of the child protection service, 10 Volunteers of Manado Dinding Community, 6 students and 2 Lecturers of the Nursing Science Program at Sam Ratulangi University Manado. This activity begins with a pre-test and ends with a post-test. The results of the pre test showed that the average correct answer was 59.43% and the wrong answer was 40.57%. While the post test results show an average of 98.67% correct answers and only 1.34% were still wrong. The conclusion of this activity is that there is an increase in children's knowledge at the Bersehati Public Market in Manado City after being given health education through educational content.